Whole mouse brain connectomics. Issue 13 (23rd November 2018) - Allan Johnson, G.; Wang, Nian; Anderson, Robert J.; Chen, Min; Cofer, Gary P.; Gee, James C.; Pratson, Forrest; Tustison, Nicholas; White, Leonard E.
Abstract: Methods have been developed to allow quantitative connectivity of the whole fixed mouse brain by means of magnetic resonance imaging (MRI). We have translated what we have learned in clinical imaging to the very special domain of the mouse brain. Diffusion tensor imaging (DTI) of perfusion fixed specimens can now be performed with spatial resolution of 45 μm 3, that is, voxels that are 21, 000 times smaller than the human connectome protocol. Specimen preparation has been optimized through an active staining protocol using a Gd chelate. Compressed sensing has been integrated into high performance reconstruction and post processing pipelines allowing acquisition of a whole mouse brain connectome in <12 hr. The methods have been validated against retroviral tracer studies. False positive tracts, which are especially problematic in clinical studies, have been reduced substantially to 28%. The methods have been streamlined to provide high‐fidelity, whole mouse brain connectomes as a routine study. The data package provides holistic insight into the mouse brain with anatomic definition at the meso‐scale, quantitative volumes of subfields, scalar DTI metrics, and quantitative tractography. Abstract : Comparison of diffusion tractography within the forelimb representation of the right primary somatosensory cortex in two murine strains: C57BL and BTBR (a murine model that bears phenotypic resemblance to human autism spectrum). Note strain‐specific differences in commissural connections and longitudinal associational connections in the ipsilateral hemispheres.